2019
DOI: 10.3390/molecules24071321
|View full text |Cite
|
Sign up to set email alerts
|

A Sample Preparation Technique Using Biocompatible Composites for Biomedical Applications

Abstract: Infectious diseases, especially pathogenic infections, are a growing threat to public health worldwide. Since pathogenic bacteria usually exist in complex matrices at very low concentrations, the development of technology for rapid, convenient, and biocompatible sample enrichment is essential for sensitive diagnostics. In this study, a cucurbit[6]uril (CB) supermolecular decorated amine-functionalized diatom (DA) composite was fabricated to support efficient sample enrichment and in situ nucleic acid preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…[31] CryA has shown the hyperCEST effect at 1 nM concentrations, [32] and hundreds of fM when combined with a bacteriophage scaffold. [33] While CryA are quite difficult to synthesize, [34] the biocompatible [35][36][37][38] and commercially available CB [6] has shown hyperCEST sensitivity down to pM concentrations [31] and has been determined to be kinetically superior to CryA as a hyperCEST agent. [39] HyperCEST with CB [6] was first demonstrated in vitro with whole blood, [40] and recently, also in vivo, but at a relatively high concentration of 10 mM.…”
Section: Introductionmentioning
confidence: 99%
“…[31] CryA has shown the hyperCEST effect at 1 nM concentrations, [32] and hundreds of fM when combined with a bacteriophage scaffold. [33] While CryA are quite difficult to synthesize, [34] the biocompatible [35][36][37][38] and commercially available CB [6] has shown hyperCEST sensitivity down to pM concentrations [31] and has been determined to be kinetically superior to CryA as a hyperCEST agent. [39] HyperCEST with CB [6] was first demonstrated in vitro with whole blood, [40] and recently, also in vivo, but at a relatively high concentration of 10 mM.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that semiconductor nanomaterials cause oxidative stress by an effective antioxidant response in a cellular environment. 13,36,37 On performing the DCFDA ROS kit test (Figure 4A), we observed that (i) the intensity of the ROS of our tested ZnO nanomaterials was 1.5 times higher than in the normal cellular environment, but it was still in the safe cellular balance range of oxidative stress, and (ii) after the HI (DMS and DMP) modification the oxidative stress of the L929 cellular environment increased, but it was still in the adaptive cellular balance range. There was growing evidence that the ROS generated by the ZnO nanomaterials (<2 times) created an adaptive balance in the eukaryotic cells due to cellular stress response, but it may cause a disorder in the prokaryotic cells.…”
Section: Antibiotic Activity Of the Hins Compositementioning
confidence: 99%
“…Currently, many research groups are working on optimizing the performance of ZnO by surface modification leading to the preparation of composites (Table S1). Among these, studies on biomolecular modification with the benefits of biocompatibility and nontoxicity are promising due to specific detection and treatment measures. , The first cross-linking reagent for conjugation and modification was reported by Hartman and Wold, where symmetrical ropelike molecular families are known to have two identical reactive ends that can tie one molecule to another by a covalent reaction. Therefore, a novel composite material prepared by combining nanomaterials and reagents for surface modification would be suitable for the enhancement of biocompatibility, antibiotic efficacy, and reduction of blood coagulation in the field of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their porous structures have mechanical, photonic, transportable, fabrication, and biocompatibility capabilities, which make this biomaterial suitable for many applications, including biosensing, energy storage, adsorption, purification, photonics, catalysis, bioseparation, and drug delivery 13 , 14 . Our previous studies have shown the potential of multifunctional materials through the modification of DE composites in biological applications 15 17 .…”
Section: Introductionmentioning
confidence: 99%